PECULIARITIES OF CREATING PROGRAMMING ENVIRONMENT WITH UNIVERSAL SUPPORT OF INTERPRETERS OF PROGRAMMING LANGUAGES SUBSETS - Lavrik, A. (Journal of Information Technologies in Education (ITE), 2011)
The article considers principles of extraction subsets of programming languages, sufficient for performing computational experiments in the certain class of problems on example of sorting algorithms.